Production, Partial Purification and Antimicrobial Activity of Red Pigment by Serratia marcescens - Gholap, Avinash B.; Gaikar, Rajendra B.; Vikhe, Amol M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Serratia marcescens are the secondary metabolite for production of red pigment. This pigment is a promising drug owing having antifungal, immunosuppressive and anti-proliferative activity. In given study optimization of LB for maximum yield of pigment production was performed. The pigment produced was partially purified to study its antimicrobial activity. The optimization for pigment production was carried out to increase pigment production using parameters viz; Incubation period, pH, Temperature, Percent inoculum, Oil substrates play a vital role in pigment production. LB media was supplemented with Sesame, Groundnut, Coconut, and Sunflower oil to enhance pigment production. The purity of pigment was checked by TLC and SGC. The partially purified form of the pigment showed antimicrobial activity against Staphylococcus aureus.